2010
DOI: 10.1108/17504971011075174
|View full text |Cite
|
Sign up to set email alerts
|

Why females do not choose computing? A lesson learned from China

Abstract: PurposeThe declining participation of young American females in computing fields negatively impacts diversity in the computing‐related workforce. While computing in China is also dominated by men, career prospects are positively perceived by Chinese women. The purpose of this paper is to investigate both countries' female gender perceptions toward computing and two influencing psychological factors, computer anxiety and computer self‐efficacy (CSE). To better understand American females' perception toward comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…A number of studies have discussed the factors that appear to make female students reluctant to study CS at university [7,9,35]. Moreover, scholars and researchers have explored why females are under-represented in Computer Science [35,62]. Others have investigated the factors that influence students' intention to pursue a CS major [12,17,36].…”
Section: Factors Influencing the Choice To Study Computer Sciencementioning
confidence: 99%
“…A number of studies have discussed the factors that appear to make female students reluctant to study CS at university [7,9,35]. Moreover, scholars and researchers have explored why females are under-represented in Computer Science [35,62]. Others have investigated the factors that influence students' intention to pursue a CS major [12,17,36].…”
Section: Factors Influencing the Choice To Study Computer Sciencementioning
confidence: 99%
“…In addition, [8] found that people who reported to have medium to high levels of computer anxiety performed less well than those with low level of computer anxiety in an examination involving the use of computers. Moreover, [27] added that computer anxiety is also considered as an affective response which [15] explained that the feelings of anxiety may be mediated by beliefs about lack of ability to use a computer knotted to a lack of mathematical and mechanical skills.…”
Section: Anxiety and Computer Anxietymentioning
confidence: 99%
“…Olatoye (2009) stated that anxiety is an intense dread, apprehension or nagging worry while Mathew (2012) explained anxiety is a natural and unavoidable reaction to a perception of danger or risk. Simsek (2011) added that computer anxiety is considered as an effective response while Laosethakul and Leingpibul (2010) explained that the feelings of anxiety may be mediated by beliefs about lack of ability to use a computer knotted to a lack of mathematical and mechanical skills. Kannan, Muthumanickam and Chandrasekaran (2016) refer computer anxiety as when a student is afraid, uneasy to use computer.…”
Section: Literature Reviewmentioning
confidence: 99%